Development of a Highly Sensitive and Selective Optical Chemical Sensor for the Determination of Zinc Based on Fluorescence Quenching of a Novel Schiff Base Ligand - Aksuner, Nur; Henden, Emur; Yilmaz, Ibrahim; Cukurovali, Alaaddin (Amer Scientific Publishers, 2010)
A sensitive new optical sensor for Zn(2+) is described. This optode is based on a novel Schiff base ligand, 2-(2-hydroxy-5-chloro)benzaldehyde-[4-(3-methyl-3-mesitylcyclobutyl)-1,3-thiazol-2yl]hydrazone, in plasticized polyvinyl chloride membrane. This sensing membrane is capable of determining Zn(2+) with a high sensitivity and selectivity over a wide dynamic range between 5.0 x 10(-7) to 1.0 x 10(-4) mol L(-1) at pH 6.0 with a lower detection limit of 2.2 x 10(-7) mol L(-1) (14.4 mu g L(-1)). The sensor can readily be regenerated with 1.0 mol L(-1) EDTA solution. In addition to high stability, the sensor shows a unique selectivity toward Zn(2+) with respect to common metal cations. The sensor was successfully applied for the determination of zinc real samples. The results obtained for the determination of zinc ions in hair samples using the proposed method was found to be comparable with the well-established flame atomic absorption method.
Keywords: Schiff Base; PVC Matrix; Fluorescence Spectroscopy; Optical Sensor; Zinc